The Idler, Volume III., Issue XIII., February 1893 : An Illustrated Monthly. Edited By Jerome K. Jerome & Robert Barr - Various; Barr, Robert, 1850-1912; Jerome, Jerome K. (Jerome Klapka), 1859-1927 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Idler, Volume III., Issue XIII., February 1893" is a collection of literary works edited by Jerome K. Jerome and Robert Barr during the late 19th century. This edition features a diverse array of narratives and articles, including fiction and commentary on various themes, reflecting the social and cultural life of the time. Notable pieces include "Cheating the Gallows" by I. Zangwill, which presents the contrasting lives and personalities of characters Tom Peters and Everard G. Roxdal, offering insight into the intricacies of friendship and societal expectations. The opening of "Cheating the Gallows" introduces readers to an odd couple, Tom Peters, a laid-back journalist, and Everard G. Roxdal, a bank manager engaged to a respectable woman. Their contrasting lifestyles$1 (BPeters' leisurely, carefree existence versus Roxdal's polished and respectable demeanor$1 (Bset the stage for an exploration of themes like companionship, societal roles, and perhaps hidden motives. The narrative hints at the complexity of their relationship, especially as Roxdal's upcoming marriage to Clara Newell adds tension. As the story unfolds, the dynamic between the two men and their interactions with Clara foreshadow potential conflict, alluding to deeper plot developments around loyalty, ambition, and personal identity. (This is an automatically generated summary.)s
Release date is 2004-05-01
Jonathan Ingram and PG Distributed Proofreaders
Keywords: London (England) -- Periodicals